Evaluierung von Agrarumweltprogrammen auf Grundlage der Umwelteffizienz landwirtschaftlicher Betriebe - Tammo Francksen; Uwe Latacz-Lohmann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2008)
– This paper sets out to develop an economic framework for ex post evaluations of agri-environmental schemes. We begin by developing a non-parametric model for estimating farm-level environmental efficiency scores. We then use this efficiency framework to devise a set of economic criteria for evaluating agri-environmental schemes. One key criterion is whether an environmental scheme has given rise to an increase in environmental efficiency scores across participating farms, relative to a counterfactual group of non participants. We finally demonstrate the potential usefulness of the framework by applying it to a fictitious multiple-objective conservation programme. The dataset is made up of 100 fictitious farms, half of which participate in the environmental programme. Each farm is characterised by a set of financial and environmental performance indicators. The results of this mock evaluation show that the proposed evaluation framework generates useful insights into the performance of the scheme and permits identification of potential improvements.
Keywords: 330; Agrarpolitik; Umweltpolitik; Wirkungsanalyse; Messung; Umweltbelastung; Nichtparametrisches Verfahren